2019
DOI: 10.1002/uog.19173
|View full text |Cite
|
Sign up to set email alerts
|

Fetal optic chiasm: three steps for visualization and measurement on routine transabdominal ultrasound

Abstract: The optic chiasm (OC) is an X-shaped structure formed by the crossing of the optic nerves in an axial view of the fetal brain. It is located in the chiasmatic cistern and it is surrounded by the Willis circle. The anterior cerebral arteries lay anteriorly, the posterior communicant arteries lay laterally and the posterior cerebral arteries are identified posteriorly. The decussation or centre of the OC corresponds to the origin of the middle cerebral arteries laterally arising from internal carotids. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…The scanning was performed by a single experienced sonographer using a Samsung WS80A (Samsung Medison, Seoul, Korea) ultrasound machine with a 1-8-MHz transabdominal transducer. The fetal OC was visualized and measured following recently published recommended practices (12). First, the operator obtained an axial image of the fetal head in the biparietal-diameter plane.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The scanning was performed by a single experienced sonographer using a Samsung WS80A (Samsung Medison, Seoul, Korea) ultrasound machine with a 1-8-MHz transabdominal transducer. The fetal OC was visualized and measured following recently published recommended practices (12). First, the operator obtained an axial image of the fetal head in the biparietal-diameter plane.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested that measurement of the ONs is not feasible because of shadowing from the sphenoid bone (8,11). However, it was reported in a recent article (12) that the ONs could be visualized on transabdominal ultrasound. Our results showed an 85.8% (310/361) success rate for measuring normal intracranial ONs, although the repeatability test result of fetal ON measurement was not satisfactory (interobserver ICC 0.798, intraobserver ICC 0.775).…”
Section: A B Cmentioning
confidence: 97%
See 2 more Smart Citations
“…[19] It is noteworthy that reference intervals determined in the study by Haratz et al are smaller than values obtained by 3D ultrasound imaging by Bault et al [7] The results we found in our study are closer to the 3D measurements of Bault et al Alonso et al showed that optic chiasm can be fully visualized by fetal ultrasonography. [20] In their study, Vinal et al showed that it would be possible to evaluate fetal optic chiasm from the coronal plane with transvaginal ultrasound. [21] However, optic nerve measurement was not defined in these studies.…”
Section: Discussionmentioning
confidence: 99%